Emerging frontiers in perovskite solar cells: Principles, performance, and pathways to commercialization - Ghosh, Souvik; Sharma, Ananda; Deka, Nitumoni; Mondal, Haraprasad; Tara, Ayush; Alali, Ahmet Sait; Nanda, Jajneswar; Kumar, Abhinav; Oza, Ankit Dilipkumar; Bhattarai, Sagar; Dakua, Pratap Kumar; Neupane, Kumar (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Over the past decade, the Perovskite Photovoltaic device has enticed significant interest because of its continuously improving power conversion efficiency (PCE), straightforward solution-based manufacturing process, lightweight and flexible properties, applicability in compact, mobile, or aerospace technologies, and utilization of low-cost, readily available components. The synergetic effect of energy-efficient fabrication techniques, optimized charge transport layers, and advanced electrode materials has propelled perovskite solar cell efficiency to surpass 25%, thanks to the production of top-grade perovskite layers. Alongside efficiency, the stability of Perovskite solar cell (PSC) has garnered remarkable recognition from researchers. This review article explores recent developments in PSC, with a specific focus on enhancing crystallinity, morphology, and synthesis techniques. The review also discusses the interfacial region between various films, such as perovskite/Electron Transport Layer (ETL), ETL/Hole Transport Layer (HTL), and HTL/electrode, which are crucial for the efficiency and environmental stability of perovskite solar cells. The review also explores the prospect of PSC technologies, including those based on tin-based, carbon-based, and polymer-based devices. The potential drawbacks of commercializing these emerging technologies are assessed.
Keywords: Perovskite solar cells (PSCs); Electron transport layer (ETL); Hole transport layer (HTL); Power conversion efficiency (PCE); ENERGY-BAND; EFFICIENT; TRANSPORT; STABILITY; ISSUES; Physics